Chapter An analysis of the transaction towards sustainable food consumption practises during the Italian lockdown for SARS-CoV-2: the experience of the Lombardy region - D'ADDARIO, MARCO (Proceedings e report, 2021)
This paper intends to investigate the behaviours adopted during this lockdown period due to SARS-CoV-2, in which most individuals have found themselves forced to carry out their daily lives within domestic boundaries, and compare them with previously practiced food-related habits. The aim is to understand whether strategies of buying, preparing and consuming food have changed with respect to established habits of 'ordinary' periods, and how these choices are linked to the psychological and emotional wellbeing/feeling experienced by individuals, to the physiological well-being of individuals and to social, environmental and economic sustainability. The analysis is based on the survey carried out by the Department of Psychology in collaboration with the interdepartmental center BEST4Food of Milano-Bicocca university.